(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The study examined arable crop farmers’ perception of rising food prices in Bayelsa State. The objectives were factors causing high cost of food prices, effect of food price hike and farmers’ perception of rising food prices in the study area. Multi-stage random sampling technique was used to select 110 respondents from 11 communities. Data were collected using structured questionnaire. The objectives were achieved using frequency, percentages, mean and analysis of variance (ANOVA). The hypotheses were tested at 5% level of significance. Findings showed that transportation cost ( = 4.68), high cost of inputs ( = 4.36), climate change ( = 4.35), reduction in currency value ( = 4.24) and insufficient storage facilities ( = 3.93) were the factors causing high cost of food prices in the study area. The result also revealed that food insecurity ( = 4.25), increased debt ( = 4.11), hunger and malnutrition ( = 4.06) and reduced profit ( = 3.45) were the effect of food price hike on the living conditions of arable crop farm households. Majority of the respondents had a very negative perception ( = 4.44) of rising food prices. It was concluded that majority of the respondents had a very negative perception of rising food prices. Hence, the study recommends that government should provide adequate infrastructure such as good roads in order to reduce the high transportation costs that constituted a major cause of high food prices in the study area.